Grading of Hydronephrosis: An Ongoing Challenge - Onen, Abdurrahman (Frontiers in Pediatrics, 2020)
The crucial point for prompt diagnostics, prompt treatment and followup of UPJ-type hydronephrosis(UPJHN) patients is hydronephrosis severity. Such many hydronephrosis grading systems as AP diameter, SFU, Radiology, UTD and Onen have been developed to evaluate hydronephrosis severity. AP diameter is a very dynamic parameter and is affected by many factors(renal pelvic configurations, hydration, bladder filling, position, respiration). Radiology grading system has the same grade-1,2,3 as SFU. Radiology grade-4 represent mild parenchymal loss while grade-5 severe parenchymal loss. However it is operator depended, not decisive and does not differentiate grade-4 and 5 clearly. All SFU grades are very variable between operators and clinicians. UTDclassification put all abnormal urinary findings together including kidney, ureter and bladder, and thus determine the risk level for infants with any urinary disease. Different renal deterioration risk occur depending on the mechanism of hydronephrosis. Therefore, SFU and UTD may result in significant confusion and misleading in determining hydronephrosis severity. SFU-4/UTD-P3 represent a considerable range of hydronephrosis severity. Minimal medullary thinning and severe cortical thinning represent same grade. This wide definition cause failure to demonstrate accurately the severity of hydronephrosis. They do not suggest who need surgery and who can safely be followed conservatively. The anatomophysiology of 4 kidney suborgans (renal pelvis, calices, medulla, cortex) are completely different from each other; each part behave differently depending on hydronephrosis severity. Upgraded Onen grading has been developed based on this basic evidence both for pre- and postnatal period. It determines spesific findings of renal damage that clearly suggest who can safely be followed nonoperatively from who will need surgery for UPJHN. Neighter AP diameter nor Radiology or SFU or UTD are gold standart to determine hydronephrosis severity. All these grading systems are affected by many factors. They do not determine the exact severity of UPJHN and thus cause permenant renal damage due to delay in surgery while may cause unnecessary surgery in some infants. Onen grading system has resolved all dysadvantages of other grading systems and promises a safer followup and prompt treatment for UPJHN. It is an accurate and easily reproducible grading that has high sensitivity and specificity.